Pronunciation Error In Retelling Procedure Text Made By 7th Grade Students Of SMP Muhammadiyah 5 Surakarta In 2013/2014 Academic Year: A Case Study - Pamungkas, Mifta, Dr. Dwi Haryanti, M.Hum, Siti Fatimah, S. Pd, M. Hum (2014)
The research paper aims at describing the type of pronunciation errors, the dominant word of pronunciation errors, and to reveal the cause of pronunciation error. The researcher uses descriptive qualitative research. The data are collected using observation, documents. The technique of analyzing the data is documentation. From the data taken from grade 7th it is concluded that from the total 30 students, the writer found many pronunciation errors, they are: pronunciation that have 47 errors data, and the dominant word of pronunciation errors have 8 data. The writer also found the cause of pronunciation error, they are: 1) cognitive reason, 2) psychological reason, 3) social reason, 4) pronunciation interference.